2022
DOI: 10.3390/diagnostics12112804
|View full text |Cite
|
Sign up to set email alerts
|

Serial Changes in Body Composition and the Association with Disease Activity during Treatment in Patients with Crohn’s Disease

Abstract: Objectives: To analyze serial changes in body composition and investigate the association between body composition changes and disease activity changes in patients with Crohn’s disease (CD). Methods: Seventy-one patients with CD who had been treated and followed-up at our institution were included. Two to four computed tomography images were acquired at baseline, and the 2–5-year, 5–8-year, and last follow-ups were selected per patient for body composition and disease activity analyses. Visceral fat area (VFA)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 44 publications
1
3
0
Order By: Relevance
“…The results of this study are consistent with the findings of Labarthe et al ( 37 ), who analyzed the correlation between body composition and disease activity level in CD patients using MRI images, although the disease activity level score (Harvey-Bradshaw) used by this team was defined according to the patients’ clinical symptoms. Similarly, the results of a recent study of 71 CD patients with activity follow-up found a negative correlation between SAI and SMI and the disease activity level ( 38 ), which is similar to our findings. In addition, we found more significant differences in body composition-related parameters when the activity levels differed more (remission vs. moderate-to-severe activity).…”
Section: Discussionsupporting
confidence: 93%
“…The results of this study are consistent with the findings of Labarthe et al ( 37 ), who analyzed the correlation between body composition and disease activity level in CD patients using MRI images, although the disease activity level score (Harvey-Bradshaw) used by this team was defined according to the patients’ clinical symptoms. Similarly, the results of a recent study of 71 CD patients with activity follow-up found a negative correlation between SAI and SMI and the disease activity level ( 38 ), which is similar to our findings. In addition, we found more significant differences in body composition-related parameters when the activity levels differed more (remission vs. moderate-to-severe activity).…”
Section: Discussionsupporting
confidence: 93%
“…Sarcopenia remained to be an independent predictor of second‐line therapy failure (OR: 3.401, 95% CI: 1.104–10.479, P = 0.033). In patients who underwent colectomy, the rate of post‐op complications was significantly higher in those with sarcopenia compared with those without sarcopenia (58.6% vs. 33.3% respectively, P = 0.037); sarcopenia alone was an independent risk factor for post‐op complications (OR: 4.157, 95% CI: 1.364–12.667, P = 0.012) in ASUC patients who underwent colectomy 109 . Another larger retrospective study of 254 patients with ASUC similarly assessed muscle mass on CT.…”
Section: Impact On Managementmentioning
confidence: 95%
“…In patients who underwent colectomy, the rate of post-op complications was significantly higher in those with sarcopenia compared with those without sarcopenia (58.6% vs. 33.3% respectively, P = 0.037); sarcopenia alone was an independent risk factor for post-op complications (OR: 4.157, 95% CI: 1.364-12.667, P = 0.012) in ASUC patients who underwent colectomy. 109 Another larger retrospective study of 254 patients with ASUC similarly assessed muscle mass on CT. It showed that patients with myopenia had a significantly higher need for rescue therapy (40.9% vs. 23.6%, P = 0.003) and a need for surgery (22.0% vs. 7.1%, P = 0.001).…”
Section: Impact On Managementmentioning
confidence: 99%
“…Recent studies have demonstrated the accurate measurement and quanti cation of adipose tissue distribution, particularly the "visceral fat area" (VFA), and muscle mass to assess the grade of myopenia using computed tomography (CT) or magnetic resonance imaging (MRI), and the strong correlation with the visceral fat mass [13][14][15] .…”
Section: Introductionmentioning
confidence: 99%